Design and Evaluation of Bilayer Matrix Tablet of Metoprolol Tartrate and Lisinopril Maleate. Issue 2 (29th September 2015) - Ijaz, Hira; Qureshi, Junaid; Danish, Zeeshan; Zaman, Muhammad; Abdel‐Daim, Mohamed; Bashir, Irfan
ABSTRACT: The objective of study was to design bilayer matrix tablet of metoprolol tartrate and lisinopril maleate. The direct compression method was used for preparation of both layers. Precompression and postcompression parameters were evaluated. USP Type II dissolution apparatus was used for the in vitro drug release study using 0.1 N HCl for immediate release of lisinopril maleate layer for 2 h and phosphate buffer at pH 6.8 for 10 h for metoprolol tartrate sustained layer. In vitro data were fitted into various kinetic models. Precompression parameters showed good flow properties of powder blend. Postcompression parameters were within compendia range. L7 (2% SSG and 3% CC‐Na) was selected for formulation of immediate release layer that showed 91.6% drug release after 10 min, and for sustained release formulation, M4 (9% pectin, 9% acacia, and 20% Eudragit L100) showed 92.5% drug release for 10 h. Most formulations of sustained layer followed Higuchi drug release kinetics. Bilayer matrix tablet of metoprolol tartrate and lisinopril maleate can be formulated for the treatment of postmyocardial infarction.